PENGARUH PROMOSI DAN INOVASI LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA UMKM FINKAN KEBAYA DI MANDALA - Tesalonika Simalango; Sri Rezeki (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
Finkan Kebaya Mandala, a Micro, Small, and Medium Enterprise (MSME) engaged in the production and provision of traditional and modern apparel, experiences relatively stable demand but significant sales fluctuations, particularly a decline in early 2025. This condition is influenced by seasonal factors, limited advertising and promotional strategies, service innovation that has not fully aligned with customer needs, and increasing competition. This study aims to analyze the influence of promotion and service innovation on consumer purchasing decisions at Finkan Kebaya in Mandala. Data were collected through interviews, literature review, observation, and questionnaires using a Likert scale. The analysis methods included normality, multicollinearity, and heteroscedasticity tests, multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results show that promotion has a positive and significant effect on purchasing decisions, contributing 26.7%, while service innovation also has a positive and significant effect with a contribution of 48.0%. Simultaneously, both variables significantly influence purchasing decisions. These findings indicate that the synergy between effective promotion and continuous service innovation is essential to improving competitiveness and encouraging consumer purchasing behavior.